White Fulani cattle of West and Central Africa - Tawah, C.L.; Rege, J.E.O. (Food and Agriculture Organization of the United Nations, 1996)
The paperreviews information on the White Fulani cattle under the headings; origin, classification, distribution, population statistics, ecological settings, utility, husbandry practices, physical characteristics, special genetic characteristics, adaptive attibutes and performance characteristics. It was concluded that the breed is economically important for several local communities in many West and Central Africa countries. The population of the breed is substantial. However, introgression from exotic cattle breeds as well as interbreeding with local breeds represent the major threat to the breed. The review identified a lack of programmes to develop the breed as being inimical to its long-term existence.